Risk factors of child sexual abuse (2015)
Purpose: To show a review of specialized literature concerning risk factors of child sexual abuse. Initially, the definitions of sexual abuse suggested by various authors are presented. Source and types of publications: Publications were obtained from libraries, periodicals and websites; the review includes articles, essays, books, chapters and laws. Point of view: Emphasis on risk contexts highlighting social, family and environmental characteristics, as well as personal features, whose presence is related to the likelihood of child sexual abuse. Conclusions: When we talk about risk factors for child sexual abuse, it is clear that, behind this reality that favors the emergence and continuity of this social scourge, there are protective conditions that, when incorporated in various actions or preventive strategies, contribute to decrease this problem.